Antimicrobial Activity of Ethanol Extract of Walang Leaves against Salmonella typhi and Candida tropicalis - Swastika Oktavia; Ayu Febi Lestari; Arini Khaerunnisa (Lembaga Pengembangan Kinerja Dosen, 2025)
Leaves of Etlingera walang (Blume) RMSm have been empirically used in traditional medicine to relieve stomach disorders and are known to contain secondary metabolites with potential antimicrobial properties. Salmonella typhi infection can cause typhoid fever with symptoms such as diarrhea and abdominal pain, while Candida tropicalis is a fungus that can infect the gastrointestinal tract and lead to digestive disturbances. This study aimed to evaluate the antibacterial and antifungal activities of the ethanolic extract of E. walang leaves against S. typhi and C. tropicalis. The antimicrobial assay was carried out using the disk diffusion method at extract concentrations of 25%, 50%, and 100%, with chloramphenicol and ketoconazole as positive controls, and DMSO as the negative control. Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, and tannins. However, the results showed that the extract did not produce inhibition zones against either test microorganism. Extract evaluation indicated a moisture content of 12.23%, total ash 13.39% (above the standard), acid-insoluble ash 1.25%, total plate count 1.8 × 10 ⁴ , and mold and yeast count 1.0 × 10 ³. The findings suggest that although the ethanolic extract of E. walang leaves contains secondary metabolites and is traditionally used for stomach ailments, it does not exhibit antimicrobial activity against S. typhi or C. tropicalis.